SURVEI TINGKAT PEMAHAMAN GURU TK PADA LITERASI SAINS DALAM PEMBELAJARAN ANAK USIA DINI - Ainin Shofiyah (JIV-Jurnal Ilmiah Visi, 2022)
The importance of learning science in children, one of which is to train children to appreciate and protect the nature in which they live, to cultivate and provide understanding and interest. Therefore, scientific literacy is an important thing that kindergarten teachers must master in the science learning process in the PAUD unit. This study aims determine to the level understanding of kindergarten teachers in scientific literacy in early childhood learning. The type of research method used is quantitative with a survey approach. The respondents of this study were 121 kindergarten teachers in Diwek District, Jombang City. The collection data technique used a test instrument from questionnaire with a Guttman scale rating. Data were analyzed by statistical test of central tendency and percentage technique through SPSS and Ms Excel. Data study have a results that showed the level understanding of kindergarten teachers on scientific literacy simultaneously obtained the highest score of 46 teachers with a high level of understanding, 54 teachers in the medium category and 21 teachers in the low category. Then the results specifically on 3 aspects of the assessment, namely (1). Understanding the nature of science, (2). Understanding scientific literacy, and (3). Understanding of science learning planning obtained the average level of understanding of teachers is in the medium category. Thus, it can be stated that the overall data results for the level of understanding of kindergarten teachers on scientific literacy have a moderate or good enough understanding. In addition, the results of this survey research can be used as the initial baseline data to determine the next step in conducting research on this topic which continues on improving the quality of teachers in scientific literacy skills and continues with the hope that it will have implications for sians learning in PAUD units.